Questionnaire survey on the clinical application of Hall technique preformed metal crowns in caries of primary molars in China - Wang, Junhui; Zhang, Baize; Chen, Yujiang; Wang, Lulu; Du, Yang; Ge, Xin; Liu, Fen; Gong, Jing; Wang, Xiaojing (Frontiers in Oral Health, 2025)
ObjectiveTo analyze the clinical application and limiting factors of the Hall technique (HT) preformed metal crowns in caries of primary molars and to provide reference for its clinical application based on a questionnaire survey.Materials and methodsFrom June to December 2022, a questionnaire was distributed to pediatric dentists through the WeChat platform using “Questionnaire Star” to analyze the clinical application and influencing factors of the HT preformed metal crowns in caries of primary molars.ResultsA total of 700 survey questionnaires were distributed, and 650 valid questionnaires were recovered, with a effectiveness rate of 92.86%. In terms of the awareness level of the HT, only 11.08% of pediatric dentists fully understood, while 19.85% of those were completely unaware; In terms of the understanding methods, classes study accounted for 47.60%, and 28.79% of pediatric dentists understood through literature; In terms of the application of the HT, 46.15% of pediatric dentists had applied it, only 11.23% had frequently applied it, and 53.85% had never applied it; In terms of the usage time, the highest proportion was between 1 and 3 years, accounting for 40.33%, and only 9.67% were over 5 years; In terms of the choosing of indications, only 26.62% of pediatric dentists could select indications correctly; Regarding the choice of treatment methods for children who do not cooperate, only 19.54% of pediatric dentists chose the HT. The education background and nature of the workplace had a statistically significant difference in the application of the HT, the number of years of application, the selection of indications, and the choice of treatment methods for children who do not cooperate.ConclusionsThe survey showed that the awareness level and application frequency of the HT were relatively low in China. The understanding methods mainly learned through classes study.Clinical relevanceIt is necessary to further promote the development of continuing education projects with the theme of clinical application of the HT and the guidance of clinical operation standards, in order to promote the clinical popularization of it in China.